Growth and poverty: policy implications for lagging states - Virmani, Arvind (2008)
This article shows that the interstate differences in poverty rates can be largely explained by differences in the per capita gross domestic products, agricultural growth and the share of the bottom 40 per cent of the population in consumption. To eliminate poverty, economic policy therefore has to accelerate growth, focus programmes on agriculture and rural development in the poorer states and target subsidies at the bottom 40 per cent. The most critical areas distinguishing state growth performance have been modern (registered) manufacturing and commerce. - Reproduced.
Keywords: Economic growth; Poverty